P33-F Acute ultrasound architectural and sEMG changes in distal biceps brachii muscle with different contraction types. Issue 7 (July 2019) - Banea, Ovidiu Constantin; Stefansson, Sigurjón; Bazán, Fernando; Ívarsson, Eysteinn; Jónasson, Aron Dalin; Ólafsson, Ingvar Hákon; Gargiulo, Paolo
Abstract : Background: Ultrasound muscle thickness (MT) measurements may offer a valid and reliable method for estimating muscle size (Abe et al., 2014). It was observed that the anterior fascicles of the distal biceps brachii (dBB) inserted to the aponeurosis at an average angle of 17° at 2 cm from the myotendinous junction (MTJ) when the elbow was extended. The angle changed to 21° with flexed elbow (Asakawa et al., 2011). Purpose of this study is to reveal the acute changes and the relationship between architectural parameters and surface EMG (sEMG) of biceps brachii muscle with different contraction types. Material and methods: Five unimpaired participants have been advised to perform 4 different exercises with their right biceps brachii: concentric contraction, eccentric contraction, isometric contraction and isokinetic contraction-extension. With relaxed muscle and the elbow at 110–120° we measured the anterior fascicle angle insertion and MT at 2 and 4 cm from the MTJ in baseline condition and after 30, 60, 90 and 120 s of effective contraction. We used Natus InVisus 12 MHz transducer. Muscle activity was recorded continuously using Kine wireless sEMG Icelandic equipment with a sensor placed on the line between the medial acromion and the cubital fossa at 1/3 from the cubital fossa. Maximal voluntary contractions were performed prior to data collection to standardize the loading history of the muscle to derive the contraction levels. Results and conclusions: Preliminary data showed 20–30% increment of MT after the 2 min concentric contraction while the anterior fascicle angle insertion increased up to 30°.